Professional identity formation among non-clinical professionals in the field of continuing medical education - Weiss, Stacy Gail (My University, 2024)
This study explored professional identity formation among non-clinical professionals in the field of continuing medical education. Specifically, two research questions examined how these professionals both define and perceive the development of their professional identities. The theoretical framework of professional identity formation was used to examine the data. It provided a lens to explore how personal values, beliefs, and experiences might integrate with the norms, values, and expectations of a professional community. A basic qualitative design was chosen, with semi-structured interviews as the primary data collection method. Interviews with 11 non-clinical professionals in continuing medical education generated thick rich data for analysis. Four main themes emerged: (a) professional disorientation (including fear and isolation), (b) imposter syndrome, (c) resilience (with risk-taking as a sub-theme), and (d) empowerment (with mentorship and community of support as sub-themes). Findings revealed that these non-clinical professionals experience professional disorientation due to a combination of unclear career paths, regulatory pressures, and the absence of formal credentials, among many other issues. Participants found it difficult to articulate their professional identities and reported a sense of fear, isolation, imposter syndrome, and professional vertigo that destabilized their sense of identity. However, resilience, mentorship, and community of support emerged as themes that empowered participants to counter these challenges and embrace their authentic selves. These findings suggest that professionals would benefit from targeted support systems such as structured mentorship programs and solid supportive networks to reduce disorientation and affirm professional identity development in those fields lacking defined career paths. The study expands on existing research and provides new perspectives on professional identity formation in multiple contexts.
Keywords: Professional disorientation; Professional vertigo; Imposter syndrome; Resilience; Empowerment; Continuing medical education